Finger Cue for Mobile Robot Motion Control - Tresna Dewi; Amperawan Amperawan; Pola Risma; Yurni Oktarina; Dicky Astra Yudha (Computer Engineering and Applications Journal, 2020)
The current technology enables automation using a robot to help or substitute humans in industry and domestic applications. This robot invasion to human life emerges a new requirement to set a method of communication between a human and a robot. One of the oldest languages is finger gesture, and this is easy to be applied method by implementing image detection that connected to the actuators of the robot to respond to human orders. This paper presents a method to navigate robots based on human fingers cue, including "Forward," "Backward," "Turn right," "Turn left," and "Stop" to generate the forward, backward, turn right, turn left, and stop motion. The finger detection is facilitated by a camera module (NFR2401L) with the image plane of 640 x 480 and 30 fps speed. The detection in coordinates x <43 and y <100, robot moves forward, in x <29 and y <100-coordinates , robot turns left, and in x <19 and y <100-coordinates , robot turns right. The experiment was conducted to show the effectiveness of the proposed method, and to some extent robot can follow human cues to navigate in its assigned location.